Surveying the Degree of Domestic Violence against Women and its effective factors in Married Women in Sabzevar - Ahmadi, Z; Mehri, A; Nadrian, H; Hashemian, M; Rahayy, Z; Mehri, A (Asian Pacific Journal of Environment and Cancer, 2018)
Background Violence against women is a global phenomenon experienced in the private and public areas of life. The aim of this study was to investigating the degree of violence and identifying the relevant factors for recognition, prevention and control of this phenomenon is essential. This study was conducted to determine the degree of domestic violence and its related factors in married women in Sabzevar in 2018. Methods In this descriptive-analytical study; 360 married women in Sabzevar were selected by cluster sampling method (10 × 40) and examined. A questionnaire was used to collect data,Its validity was determined by the panel of experts and its reliability was determined by Cronbach’s alpha(0.65-0.83)and self-report completed for data analysis, descriptive tests and regression-based path analysis were used. Results According to the results, the average rate of violence against women was reported by 85.40 ± 39.55 out of a total of 290 grades. Social factors (β = 0.072), family factors (β = 0.075), and related factors of couples (β = 0.640) which explained 39% of total variance of violence. Among these factors, the effect of factors related to couples was more than other factors. Violence rate against women includes legal violence (19%), verbal violence (18%) and emotional violence (15%) were the most significant type of violence in the community. Conclusion The degree of violence in the investigated society was significant. Due to its consequences, the degree of violence in the population should be reduced. Considering the most important factors affecting the occurrence of violence related to couples, such as the lack of training of couples and the lack of ability of couples to control anger and some of the strategies of women to deal with violence. Therefore, it is necessary for the relevant authorities to intervene in empowering couples to deal with this problems. The amount of referral to the counselor for solving very few issues should be increased by taking appropriate measures from the relevant authorities. Considering couples’ suggestions such as reducing unemployment and economic problems, and also the government can help reduce the risk of violence between couples.